Estimating Production Functions of Multiproduct Firms - Nelli Valmari (The Research Institute of the Finnish Economy (ETLA), 2016)
Despite the fact that multiproduct firms constitute a considerable share of firms and account for an even greater share of production, virtually all production function estimates are based on the assumption that firms are single-product producers. The single-product assumption is made due to lack of data on input allocation across the various product lines multiproduct firms operate. I provide a method to estimate product-level production functions without observable input allocations. The empirical application and Monte Carlo simulations show that the single-product firm assumption leads to biased parameter and productivity estimates and overestimated productivity differences between firms.
Keywords: D24; L11; L25; 330; Multiproduct firm; production function; productivity